2004
DOI: 10.1152/ajprenal.00444.2003
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RET leads to vesicoureteric reflux in mice

Abstract: , a tyrosine kinase receptor essential for kidney development, has recently been shown to be important for the formation of the urinary tract. When RET is overexpressed in the HoxB7/Ret transgenic mouse, kidneys are small and cystic, and in some of the mice, the ureters are grossly dilated. Here, we report that the observed ureteral dilatation is associated with the urinary tract abnormality vesicoureteric reflux (VUR), in which urine flows retrogradely from the bladder to the ureter. Reflux was determined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 31 publications
2
58
0
1
Order By: Relevance
“…A shortening of the intramural segment, or ureter orifices joining the trigone abnormally, can be caused by sprouting of the ureteric bud from the Wolffian duct from a location more cranial or caudal than normal (Mackie and Stephens, 1975;Pope et al, 1999;Stephens, 1983) as seen in several mouse models (Basson et al, 2005;Batourina et al, 2005;Grieshammer et al, 2004;Kume et al, 2000;Lu et al, 2007;Miyazaki et al, 2000;Yu et al, 2004), or by abnormalities in ureter transposition, at the time when the ureter normally separates from the Wolffian duct (Batourina et al, 2005). Intrinsic ureteral abnormalities, such as a failure in muscle differentiation, can also result in reflux owing to faulty urine transport or peristalsis (Airik et al, 2006;Chang et al, 2004;Yu et al, 2002).…”
Section: Application Of This New Model To Human Diseasementioning
confidence: 99%
“…A shortening of the intramural segment, or ureter orifices joining the trigone abnormally, can be caused by sprouting of the ureteric bud from the Wolffian duct from a location more cranial or caudal than normal (Mackie and Stephens, 1975;Pope et al, 1999;Stephens, 1983) as seen in several mouse models (Basson et al, 2005;Batourina et al, 2005;Grieshammer et al, 2004;Kume et al, 2000;Lu et al, 2007;Miyazaki et al, 2000;Yu et al, 2004), or by abnormalities in ureter transposition, at the time when the ureter normally separates from the Wolffian duct (Batourina et al, 2005). Intrinsic ureteral abnormalities, such as a failure in muscle differentiation, can also result in reflux owing to faulty urine transport or peristalsis (Airik et al, 2006;Chang et al, 2004;Yu et al, 2002).…”
Section: Application Of This New Model To Human Diseasementioning
confidence: 99%
“…the phenotype of this model is thought to corroborate the hypothesis that abnormal ureteric bud position disrupts ureterovesical junction formation. 66 similarly, reduced PaX2 signaling caused by a heterozygous Pax2 mutation has been shown to result in shortened intravesical ureters, caudally shifted ureteric buds, reduced bud branching, small hypoplastic kidneys with reduced nephron number and particularly vur. 51,67 the transcription factor Lim1 (also known as homeobox protein Lhx1) is a homeobox gene expressed in the organizer region of mouse embryos.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 94%
“…Although there is only limited evidence that links mutations in Ret to kidney and urinary tract malformations in humans [Loré et al, 2000[Loré et al, , 2001 and Ret mutations have not been identified in the only VUR family studied [Shefelbine et al, 1998], several investigations with animal models suggested that Ret dysfunction may be responsible for UB branching, distal ureter abnormalities, and VUR [Shakya et al, 2005;Yu et al, 2004, Batourina et al, 2002Schuchardt et al, 1996]. UB outgrowth is inhibited in ret-null mice; however, their metanephric mesenchyme is still responsive to inductive signals [Murawski and Gupta, 2006;Costantini and Shakya, 2006;Pachnis et al, 1993].…”
Section: Introductionmentioning
confidence: 99%